Implikasi Aliran Utama Filsafat Pendidikan Islam Terhadap Metodologi Pembelajaran - Sufiana, Iffatul Izza; Darnoto, Darnoto; Al Mufti, Alex Yusron (Indonesia, 2024)
There are three main schools in Islamic educational philosophy in this research. First, the conservative sect, with the main figure being al-Ghazali. This school tends to use various learning methods, including hasanah models or uswatun, habituation, good relationships, self-introspection, and stories or qishoh. Second, the religious-rational flow, with the main figure being the Ikhwan al-Shafa. This school tends to prioritize group learning methods. Third, the pragmatic school, with the main figure being Ibn Khaldun. This school prioritizes a learning method known as learning by doing or direct practice. The aim of this research is to analyze the main schools of Islamic educational philosophy and identify their implications for learning methodology. This research uses descriptive methods to study and analyze certain phenomena. It is a qualitative research method that focuses on understanding the concept or phenomenon being discussed. The data used is relevant literature, such as journals and books related to Islamic education. The data collection method is literature study, and the data verification technique is the content analysis method. The results of this research show that each school of Islamic educational philosophy has a unique approach to learning methodology. The conservative school places more emphasis on traditional methods, the religious-rational school tends more towards group discussions, and the pragmatic school encourages learning through direct practice. Thus, Islamic education can be adapted to various learning methods according to the values ​​and goals of each philosophical school.